On the null one-way solution to Maxwell equations in the Kerr space-time - Пелих, В.; Тайстра, Ю.; Pelykh, V.; Taistra, Y. (Lviv Politechnic Publishing House, 2018)
Розглянуто рівняння Максвелла з умовою однонапрямленого ізотропного поля в просторі Керра. Для кожного ЗДР, отриманого після застосування методу відокремлення змінних, накладено деякі граничні умови. Це приводить до обмеженості константи відокремлення ω та до фіксованості азимутального числа m значеннями ±1. Розглянута задача показує фізичну застосовність особливих розв’язків і становить інтерес для астрофізики.

We consider Maxwell equations with the null one-way condition in the Kerr space-time. For each ODE equation, which is obtained by using the method of separable variables, we impose some boundary conditions. This is resulting in the boundedness of the separation constant ω and in fixing the azimuthal number m by the values ±1. The problem considered demonstrates physical applicability of singular solutions and presents an interest for astrophysics.
Про однонапрямлений ізотропний розв’язок рівнянь Максвелла у просторі Керра
Keywords: алгебраїчно спеціальне поле; рівняння Максвелла; простір-час Керра; algebraically special field; Maxwell equations; Kerr space-time; 537.876; 517.927.2; 517.955